Pengembangan E-Book Cerita Bergambar pada Materi Struktur Atom dengan Pendekatan Saintifik - Siti Munawaroh; Epinur; Firdiawan Ekaputra; Yusnidar; Isra Miharti; Febbry Romundza (Mataram University, 2026)
The material on atomic structure contains abstract concepts so it is often considered difficult by students. Therefore, innovative and engaging learning media are needed to help students understand the material more effectively. One alternative is the development of a pictorial story e-book integrated with a scientific approach to encourage critical and scientific thinking skills. The research aimed to determine the development process and feasibility of a pictorial story e-book on atomic structure material using a scientific approach. The research used the Lee and Owens development model. The instruments used were interview guidelines and questionnaires. The developed product was validated by a material expert and a media expert, assessed by a chemistry teacher, and tested on a small group of students. The data were analyzed using qualitative and quantitative analysis techniques. The results showed that the average scores from the material expert and media expert were 4,5 and 4,57, respectively, both categorized as “very feasible”. The teacher assessment obtained an average score of 4,8 with the category “very good”, while students responses showed a feasibility percentage of 83,14%, categorized as “very good”. Therefore, the developed e-book is considered feasible as a chemistry learning material.